A Glimpse and Perspective of Current Organosilicon Chemistry from the View of Hydrosilylation and Synthesis of Silicon-Stereogenic Silanes - Ye, Fei; Xu, Li-Wen (Synlett, 2021)
Silicon and its related organosilicon chemistry has become a mainstay in synthetic chemistry as they can participate in numerous organic transformations. Due to space limitations, this perspective is focused on a glimpse of current organosilicon chemistry from the view of catalytic hydrosilylation and synthesis of silicon-stereogenic silanes. The progress of the two topics fully illustrates that organosilicon chemistry has become a hot research field in recent years and will play a greater role in academic research and industrial applications of silicon element in the future.1 Introduction2 Hydrosilylation3 Catalytic Constructions of Silicon-Stereogenic Centers4 Conclusion and Perspective
Keywords: organosilicon; hydrosilylation; silicon-stereogenic center